Bakteri dalam proses produksi gas metana dari tumpukan sampah organik: Kajian pustaka - Sulastri Putri Imani; Agisni Setiawati; Lutfia Oktaviani; Hertien Koosbandiah Surtikanti; Didik Priyandoko (Bioculture Journal, 2024)
Methane gas is a gas that occurs naturally on earth and is formed in piles of rubbish due to the large number of bacteria that nest in it. This article aims to discuss the formation of methane gas originating from piles of organic waste. The type of research method in this article uses a comparative method of journals and articles from within the country and abroad. Based on the results of the study, it was found that there is methane gas formed from piles of organic waste that undergoes an anaerobic decomposition process and there are several bacteria that play a role in the process of forming methane gas, such asEnterobacter, Pseudomonas, Bacillus, Streptomyces and Streptococcus which is the most dominant bacteria in organic waste.